Mad dogs - Muchamore, Robert (London : Hodder Children's Books, 2014)
When two gangs from the British underworld start a turf war, James Adams, who works for Cherub, must infiltrate the most dangerous gang of all to help the police.
Young Adult
Young Adult
Keywords: Gangs -- Juvenile fiction; Adventure and adventurers -- Fiction; Gangs -- Fiction; Spies -- Fiction; Adventure fiction; Gangs -- Fiction; Spy stories; Adventure fiction; Spy stories